Four new species of the genus Diaphorus (Diptera: Dolichopodidae) from China - Wang, Mengqing; Yang, Ding; Grootaert, Patrick (Zootaxa, 2006)
Four species of Diaphorus Meigen are described as new to science: Diaphorus guangdongensis Wang, Yang and Grootaert, sp. nov., D. jinghongensis Wang, Yang and Grootaert, sp. nov., D. longiseta Wang, Yang and Grootaert, sp. nov. and D. ruiliensis Wang, Yang and Grootaert, sp. nov. Diaphorus tongshiensis Yang is transferred to Trigonocera. And new data on distribution are reported for nine known species. A key to the species of Diaphorus from the Chinese mainland is presented, and the distribution of the genus in the Chinese mainland is discussed.